2021
DOI: 10.1016/j.mbplus.2021.100057
|View full text |Cite
|
Sign up to set email alerts
|

The Nrf2 transcription factor: A multifaceted regulator of the extracellular matrix

Abstract: The transcription factor nuclear factor-erythroid 2-related factor 2 (Nrf2) is widely recognized as a master regulator of the cellular stress response by facilitating the transcription of cytoprotective genes. As such, the Nrf2 pathway is critical in guarding the cell from the harmful effects of excessive reactive oxygen species/reactive nitrogen species (ROS/RNS) and in maintaining cellular redox balance. While excessive ROS/RNS are harmful to the cell, physiological levels of ROS/RNS play important roles in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 131 publications
(171 reference statements)
0
14
0
Order By: Relevance
“…Our data revealed that overexpression of Egr-1 significantly reduced the protein levels of p62 in macrophages during P. aeruginosa infection, which confirmed the role of Egr-1 in regulation of P. aeruginosa -induced autophagy in macrophages. The transcription factor NRF2 is a master regulator of cytoprotective responses to environmental stresses ( Hiebert, 2021 ), and is tightly regulated by Keap-1, which targets NRF2 for ubiquitination and degradation ( Jiang et al., 2015 ). Furthermore, the Keap1-interacting region domain of p62 binds to Keap-1, leading to dissociation of NRF2 from Keap-1, allowing NRF2 nuclear translocation and target gene expression ( Jiang et al., 2015 ; Tonelli et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our data revealed that overexpression of Egr-1 significantly reduced the protein levels of p62 in macrophages during P. aeruginosa infection, which confirmed the role of Egr-1 in regulation of P. aeruginosa -induced autophagy in macrophages. The transcription factor NRF2 is a master regulator of cytoprotective responses to environmental stresses ( Hiebert, 2021 ), and is tightly regulated by Keap-1, which targets NRF2 for ubiquitination and degradation ( Jiang et al., 2015 ). Furthermore, the Keap1-interacting region domain of p62 binds to Keap-1, leading to dissociation of NRF2 from Keap-1, allowing NRF2 nuclear translocation and target gene expression ( Jiang et al., 2015 ; Tonelli et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…NRF2 is another important orchestrator of the oxidative stress response and which acts as a transcription factor ( He et al, 2020 ). This important stress sensor has been shown to be required for the transcriptional regulation of several matrisome genes, including collagen I, III, and laminin α1 chain genes ( Hiebert et al, 2018 ; Hiebert, 2021 ), raising the possibility that in the presence of oxidative stress, NRF2 may control ECM remodeling ( Figure 3A ). As mentioned above, the transcriptional regulation of ECM components may also be mediated directly or indirectly via the transcription factors p53 and p73, both playing important roles sensing oxidative stress and DNA damage ( Holmstrom et al, 2014 ; Pflaum et al, 2014 ; Williams and Schumacher, 2016 ; Figure 3A ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, recently reported evidence that Nrf2 may protect cells against DNA damage by mechanisms other than anti-oxidation that preserve genomic integrity [ 82 ] could justify the ROS-independent Nrf2-mediated protection against UVB geno- and cytotoxicity observed in our cell model. Moreover, given the established ability of Nrf2 to directly regulate the expression of matrisome-coding genes [ 83 , 84 ], Nrf2 activation in human dermal fibroblasts could result in the production of an extracellular matrix that may protect cells from UVB-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%